Pain Prevalence in a Pediatric Hospital: Raising Awareness during Pain Awareness Week. (2014) - Harrison, Denise; Joly, Cynthia; Chretien, Christine; Cochrane, Sarah; Ellis, Jacqueline; Lamontagne, Christine; Regis, Vaillancourt
Abstract : BACKGROUND: Despite the evidence and availability of numerous validated pain assessment tools and pain management strategies for infants and children, their use remains inconsistent in clinical practice. OBJECTIVES: To describe the prevalence of pain, pain assessment and pain management practices at a tertiary pediatric hospital in Canada. METHODS: The cross-sectional study design involved a combination of interviews with children and/or caregivers, and chart audits in five inpatient units. Information regarding pain intensity, painful procedures and pain management strategies was obtained from children and/or caregivers by interview. Patient charts were reviewed for information regarding pain assessment, pain scores, and pharmacological and nonpharmacological interventions. RESULTS: Sixty-two children (four days to 17 years of age) participated. Most children or their caregivers (n=51 [84%]) reported that pain was experienced during their hospitalization, with 40 (66%) reporting their worst pain as moderate or severe. Almost one-half reported analgesics were administered before or during their most recent painful procedure. Nineteen (32%) reported sucrose, topical anesthetics or nonpharmacological interventions were used; however, they were documented in only 17% of charts. Pain scores were documented in 34 (55%) charts in the previous 24 h. The majority of the children or their caregiver (n=44 [71%]) were satisfied with pain management at the study hospital. CONCLUSIONS: Most infants and children had experienced moderate or severe pain during their hospitalization. Analgesics were frequently used, and although nonpharmacological strategies were reported to be used, they were rarely documented. Most parents and children were satisfied with their pain management.